Burden of diagnosed and undetected hyperkalemia in Spain: Clinical characteristics, management, healthcare resource utilization, and costs - José Luis Gorriz; Roberto Alcázar; Patricia de Sequera; Enrique Morales; Miquel Blasco; Marco Montomoli; Alberto Ortiz (Journal of Nephrology, 2026)
Abstract Background Management of hyperkalemia (HK) is challenging and suboptimal. This study analyzed the prevalence of HK and undetected HK, as well as management, clinical outcomes, healthcare resource utilization (HCRU), and costs. Methods Observational study comprising cross-sectional and retrospective analyses using secondary data from electronic health records (608,514 adults) from BIG-PAC database. The population comprised adults (n=7006) with a diagnostic code for HK, potassium >5.0 mmol/L and/or treatment for HK from January 2013 to December 2020, and follow-up ≥2 years. Index date was defined as the first HK event and undetected HK when diagnosis and/or treatment were not observed despite potassium >5.0 mmol/L at index date. Results The prevalence of HK was 1.15%, of which 0.77% was undetected. Patients with undetected HK (vs diagnosed HK) were younger and less frequently had atherosclerotic cardiovascular disease (20.0% vs 24.1%; p<0.001) and chronic kidney disease (10.8% vs 42.4%; p<0.001). In undetected HK, 58.7% had mild, 35.8% moderate, and 5.4% severe HK. Regarding outcomes, 10.9% and 18.8% (p<0.001) died, and annual hospitalization rates were 15.6% and 33.1% (p<0.001), respectively. Outcomes were more common in diagnosed HK vs undetected HK. Annual costs per patient were higher in diagnosed HK vs undetected HK (€7615 [6381] vs €5005 [4619], USD9241.6 [7743.9] vs USD6074.1 [5605.6]; p<0.001). Conclusions Around 1% of patients in Spain had HK; of these, two-thirds were undetected, including patients with moderate-to-severe HK. Despite lower comorbidity burden, these patients experienced substantial clinical events and suboptimal use of cardio-renal protective therapies.